Über die Reduzierbarkeit eines zweidimensionalen Systems von Differentialgleichungen - Merkys, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Меркис. О приводимости одной двумерной системы дифференциальных уравненийV. Merkys. Vienos dvimatės diferencialinių lygčių sistemos redukavimas